Gouy va chowgan mach by the Ghasem Gonabady - Zahra Ekhtiari (متن شناسی ادب فارسی, 2016)
The correction of “ Gouy va chowgan” (karnameh)made by the Ghasemi Gonabady published as enclosed to two volumes of seasonal journal of Ayeneye Mirath. This manuscript is aimed to make a critical correction on the matter with respect to the correctors, some points must need modification including: the year of versifying the “Gouy va chowgan mathnavi” is 947 instead of 977. The birthday of the Ghasemi Gonabadi mistakenly noted at 930, while versifying of Mathnavi of Shah Esmael Nameh “ is 940,” the Gouy va chowgan “ and “ Leili va Majnun was versified in 947, “ Shahrokh Nameh “,” Khosrow va Shirin “ and ShahTahmasbnameh “ in 950. Furthermore, the scientific method hasn’t been applied in the correction of the book especially in the preface and also the correctional method throught the book is not uniform and even sometimes the citations from other manuscripts are in the square bracket, but other times aren&#39t. Even the important part from different manuscript is not shown as footnote or inside the manuscript. The present research has corrected the errors and faults of the correctors based on a logical and scientific method.